Pengaruh Kepemimpinan dan Stres Kerja Terhadap Kinerja Karyawan pada PT Erafone Artha Retailindo Tangerang Selatan - Imam Dermawan; Lili Sularmi (Universitas 45 Surabaya, 2024)
The method used is a quantitative method with a descriptive approach. The sampling technique used was Non Probability sampling with a sample size of 55 respondents. The purpose of this research is to determine the influence of leadership and work stress on employee performance at PT Erafone Artaha Retailindo South Tangerang either partially or simultaneously. In collecting data using observation techniques and distributing questionnaires. Data analysis uses validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficient analysis, coefficient of determination analysis, and hypothesis testing. The research results show that leadership has a significant effect on employee performance with the regression equation Y = 11.839 + 0.805. Hypothesis testing obtained tcount > ttable or (4.488 > 0.266). Thus H01 is rejected and Ha1 is accepted. This means that there is a significant influence between leadership on employee performance. Job Stress has a significant effect on Employee Performance with the regression equation Y = 0.994 + 0.940 X2. The correlation value is 0.910. This means that the two of them have a very strong level of relationship with a coefficient of determination of 8.29%. Hypothesis testing obtained tcount > ttable or (16.017 > 0.266). Thus H02 is rejected and Ha2 is accepted. This means that there is a significant influence between Job Stress on Employee Performance. Leadership and Job Stress have a significant effect on Employee Performance with the regression equation Y = 1.567 + (-0.024) X1 + 0.949 X2. The correlation value is 0.900. This means that the independent variables and related variables have a very strong level of relationship with a coefficient of determination of 82.9% and the hypothesis test obtained an Fcount value of 125.999 > Ftable 3.17. Thus H03 is rejected and Ha3 is accepted. This means that there is a significant simultaneous influence between Leadership and Job Stress on Employee Performance at PT. Erafone Artha Retailindo Tangsel.